The association between weight change patterns and obesity-related complex multimorbidity: evidence from NHANES - Gong, Hong-Jian; Tang, Xingyao; Zhou, Jian-Bo (Frontiers in Endocrinology, 2024)
Objective Obesity is a major risk factor for non-communicable diseases (NCDs), which has been the leading cause of death nowadays. The aim of this study is to examine the association between total changes in body mass index (BMI) across adulthood and the risk of obesity-related complex multimorbidity in elderly, characterizing the capacity of BMI waves in predicting major chronic diseases. Methods In this retrospective study, 15,520 participants were analyzed from the National Health and Nutrition Examination Survey (NHANES) from 1999 and 2018. BMI was categorized as obesity (≥30.0 kg/m²), overweight (25.0–29.9 kg/m²), normal weight (18.5–24.9 kg/m²), and underweight (<18.5 kg/m²). Odds ratios (ORs) with 95% confidence interval (CIs) for the relationship between BMI change patterns and major health outcomes included hypertension, cancer, chronic obstructive pulmonary disease, cardiovascular disease, and diabetes, and population attributable fractions (PAFs) of BMI were evaluated. Results In comparison with participants who remained non-obese, those who are stable obese showed the highest risks of developing at least one chronic disease in later life, with odds ratios of 2.76 (95% CI: 2.20 to 3.45) from age 25 years to 10 years before baseline, 2.90 (2.28 to 3.68) from age 25 years to baseline, and 2.49 (2.11 to 2.95) in the 10-year period before baseline. Moving from non-obese to obese weight-change pattern in all periods (from age 25 years to 10 years before baseline: OR = 1.82; 95% CI, 1.57 to 2.11; from age 25 years to baseline: OR = 1.87; 95% CI, 1.59 to 2.19; from 10 years before baseline to baseline: OR = 1.62; 95% CI, 1.26 to 2.08) and moving from obese to non-obese, the 10-year period before baseline (OR = 1.89; 95% CI, 1.39 to 2.57) was associated with increased risk of chronic diseases. Midlife obesity status can explain the 8.6% risk of occurrence of the chronic diseases in elderly. Conclusions Maintaining a stable healthy weight and losing weight in early adulthood and midlife are important for better life quality during the aging process. More effective strategies and policies to reduce the prevalence of obesity are needed.